Introducing Ferrous Sulfate to Cattle Manure and Corn Straw Composting Reduces Greenhouse Gas Emissions and Ammonia Volatilization - Yucong Geng; Muhammad Amjad Bashir; Hongyuan Wang; Jungai Li; Qurat-Ul-Ain Raza; Weijie Kan; Shuo Tian; Abdur Rehim; Longcheng Yang; Hongbin Liu (Agronomy)
Composting is a well-known method for waste management, but it causes greenhouse gas emissions. Various techniques have been used to reduce emissions and improve the quality of compost, but they resulted in an increased composting time. Keeping in view the above points, the current study aimed to reduce the composting time and gas emissions along with improving the nutritional value of compost using FeSO4 as an additive to cattle manure and corn straw composting. Seven treatments were established, including control (CK) without FeSO4 and six levels of FeSO4 (0.25%, 0.50%, 1%, 2%, 4%, 8%). The results revealed that FeSO4 reduced the CH4 (36.1–36.7%), H2S (10.7–34.5%), N2O (17.2–48.5%), and NH3 (18.3–69.0%) emissions compared to CK. In addition, the total N (8.4–40.0%) content in compost products was also improved. The study showed that a higher dose of applied FeSO4 can significantly reduce emissions, but it reduces the temperature at the start of composting resulting in an increase in the composting time, while the lower dose (0.5–1%) also has the capability to reduce the emissions compared with the control without negatively affecting the temperature rise. The study concludes that using 0.5–1% of FeSO4 can effectively utilize its inhibitory action of decomposition that mitigates gas emissions and prepares an N-enriched compost.